PERCEPTIONS ABOUT TEACHER’S PROFESSION, FAMILY ENVIRONMENT, SELF-EFFICACY, AND PEERS ON INTEREST TO BECOME TEACHER AMONG FACULTY OF ECONOMICS STUDENTS - Azalia, Farah Cantika; Wolor, Christian Wiradendi; Usman, Osly (Faculty of Economics and Business, Universitas Negeri Jakarta, 2023)
The purpose of this study was to determine the direct and indirect influence between the perceptions about teacher’s profession, family environment, self-efficacy, and peers on the interest in becoming a teacher in students of the FE UNJ 2019, either partially or simultaneously. This research design is a quantitative approach to the survey method. Data collection technique with a questionnaire using a Likert scale. The data analysis technique was using multiple linear regression using SPSS 24. This study used the